Resilience processes within the school context of adolescents with sexual violence history1 - Pessoa, Alex Sandro Gomes; Coimbra, Renata Maria [UNESP]; Noltemeyer, Amity; Bottrell, Dorothy (Faculdade de Educação da Universidade Federal de Minas Gerais, 2017)
This study examines the school context of adolescents with a sexual violence history, highlighting their perceptions of protective and vulnerability mechanisms within a social ecological resilience framework. The study was conducted in a youth service agency located in a mid-sized city in the inner of Sao Paulo state. Initially, 31 male and female adolescents victims of sexual violence, aged 12-18, answered survey items assessing resilience processes. Based on their responses, a subgroup of seven adolescents was selected to participate in individual semi-structured interviews addressing the role of school in their lives. Five key themes were identified in the data, with two overarching categories emerging: ‘evaluation of school structure’ and ‘formative processes through diversity and difference’. Exploration of interview excerpts within these categories revealed that schools occupy an ambivalent space in terms of risk and protective factors in the participants’ lives, with predominately negative social indicators emerging.

Esta pesquisa investiga o contexto escolar de adolescentes com histórico de violência sexual, enfatizando suas percepções em relação aos mecanismos de proteção e vulnerabilidade a partir de abordagem ecológica de resiliência. O estudo foi realizado em um programa social localizado numa cidade do interior do estado de São Paulo. Inicialmente, 31 adolescentes, de 12 a 18 anos, de ambos os sexos e com histórico de violência sexual responderam um questionário que avaliou os processos de resiliência. Baseado nessas repostas, um subgrupo de sete adolescentes foi selecionado para participar de entrevistas semiestruturadas que versavam sobre o papel das escolas em suas vidas. Cinco temas foram identificados a partir desses dados, abrangendo duas categorias nomeadas como “avaliação da estrutura escolar” e “processos formativos através da diversidade e diferença”. A exploração dos conteúdos das entrevistas revelou que as escolas ocupam um espaço ambivalente em termos dos fatores de risco e proteção na vida dos participantes, predominando indicadores sociais negativos.
Processos de resiliência no contexto escolar de adolescentes com histórico de violência sexual
Keywords: Resilience; Sexual violence; School; Risk; Protection.; Resiliência; Violência sexual; Escola; Risco; Proteção.